Innovations in the prevention and treatment of postpartum hemorrhage: Analysis of a novel medicines development pipeline database. (28th June 2022) - McDougall, Annie R.A.; Goldstein, Maya; Tuttle, Andrew; Ammerdorffer, Anne; Rushwan, Sara; Hastie, Roxanne; Gülmezoglu, A. Metin; Vogel, Joshua P.
Abstract: Background: A significant barrier to improving prevention and treatment of postpartum hemorrhage (PPH) is a lack of innovative medicines that meet the needs of women and providers, particularly those in low‐and middle‐income countries (LMICs). The Accelerating Innovation for Mothers (AIM) project established a new database of candidate medicines under development for five pregnancy‐related conditions between 2000 and 2021. Objective: To systematically identify and rank candidates for prevention and treatment of PPH. Search Strategy: Adis Insight, Pharmaprojects, WHO ICTRP, PubMed, and grant databases were searched to develop the AIM database. Selection Criteria: AIM database was searched for candidates being evaluated for PPH prevention and treatment, regardless of phase. Data Collection and Analysis: Candidates were ranked as high, medium, or low potential based on prespecified criteria. Analysis was primarily descriptive, describing candidates and development potential. Main Results: Of the 444 unique candidates, only 39 pertained to PPH. One was high potential (heat‐stable/inhaled oxytocin) and three were medium potential (melatonin, vasopressin and dofetilide via nanoparticle delivery). Conclusion: The pipeline for new PPH medicines is concerningly limited, lacking diversity, and showing little evidence of novel technologies. Without significant investment in early‐phase research, it is unlikely that new products will emerge. Synopsis: A new database of maternal medicine development shows few new PPH candidates are in the pipeline. Significant investment is needed, particularly in early‐phase research.